القضية القبرصية...والصراع التركي – اليوناني في ظل الموقف الدولي1960-1994 (دراسة تاريخية) Cyprus issue ... Turkish - Greek conflict In light of the international situation 1960-1994 (historical study) - Ahmed Jassim Ibrahim Hamid أحمد جاسم ابراهيم حميد (Journal Of Babylon Center For Humanities Studies, 2016)
The Cyprus issue is one of the main problems that Turkey attaches special importance to Turkey and are affected by the positions of other countries on the issue was negatively or positively, because it constitutes a violation of its national security as Turkey itself is responsible for ensuring the protection of the Turkish community in Cyprus. Either on the part of Greece, the Cyprus issue at the center of the most important Greek foreign policy as axes that the position of other countries on this issue is one of its view that the main criterion when approaching or moving away from these countries. Hide the island of Cyprus in the eastern Mediterranean roots of the bloody conflict almost constant between naughty population of the Greeks and the Turks, who gathered without peaceful coexistence, the circumstances of history, migration, geographical neighbors, the two countries, the motherland Turkey, and Greece. Disagreement and misunderstanding between them has arrived at the end of civil wars, and we can go back the reasons for disagreement and conflict to that population structure that characterizes the people of the island as it includes binational rival religiously and historically, Turkish, one, Greek and the other, as well as that this problem of concern to politicians Pal in Greece ..latter-day to the issue of the political balance of power within the island only, but also stems from the common features of the political system on the island since its independence in 1960 and imposed by the three countries, Greece, Turkey and Britain.